2013
DOI: 10.1097/cej.0b013e328361625d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of upregulated DR-nm23 expression on invasion and metastasis in colorectal cancer

Abstract: To explore the role of DR-nm23 in the regulation of colorectal cancer invasion and metastasis. Immunohistochemistry assay and in-situ nucleic acid hybridization were carried out to analyze the protein and mRNA expression of DR-nm23 in patient samples. The molecular cloning technique was applied to construct the recombinant lentiviral expression vector pGC-FU-DR-nm23-GFP. Lentiviral infection was used to introduce overexpression of exogenous DR-nm23 in SW620 colorectal cancer cells. Both in-vitro cell experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…The expression of DR-nm23 in colorectal cancer tissue was significantly lower compared with that in adenoma and normal tissue. Therefore, the expression status of DR-nm23 may act as a potential prognostic factor in patients with colorectal cancer, and it may be involved in the regulation of differentiation of colorectal cancer cells (12). At the invasive front of colon carcinoma, nm23-H1 levels were also reduced or lost, and its downregulated expression was closely associated with the invasion and metastasis of colorectal cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DR-nm23 in colorectal cancer tissue was significantly lower compared with that in adenoma and normal tissue. Therefore, the expression status of DR-nm23 may act as a potential prognostic factor in patients with colorectal cancer, and it may be involved in the regulation of differentiation of colorectal cancer cells (12). At the invasive front of colon carcinoma, nm23-H1 levels were also reduced or lost, and its downregulated expression was closely associated with the invasion and metastasis of colorectal cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analysis was performed on 21 studies selected. Finally, 16 studies published from 1999-2014 were incorporated into our meta-analysis (Feng et al, 1999;He et al, 2000;Yu et al, 2000;Liu and Wang, 2001;Wang et al, 2001;Zhen et al, 2002;Zhang et al, 2003;Su and Li, 2004;Liu et al, 2005;Ba, 2006;Gao, 2006;Chen et al, 2007;Song et al, 2010;Wu et al, 2013;Qu et al, 2013;Cui et al, 2014). The baseline characteristics and NOS scores of the 16 eligible studies are summarized in Table 1 …”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for the origin and development of CRC remains unclear. Previous studies have shown that inactivation of NM23 plays an important role in the development of CRC (Wu et al, 2013;Qu et al, 2013). We explored the correlation between NM23 expression, tumor pathology, and tumor prognosis to better understand the influence of NM23 status on CRC progression and survival.…”
Section: Introduction Nm23 Expression and Crc In Asiansmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon developing chemically induced liver cancer, Nme1-deficient mice formed significantly greater lung metastases than wild-type mice (Boissan et al 2005), confirming a metastasis suppressor activity. Recent articles have expanded the breadth of metastasis suppression to Nme1 in UV radiation-induced melanoma (Jarrett et al 2013) and lung cancer (Fan et al 2013) and to Nme3 (also named Nm23-DR) in colorectal cancer (Qu et al 2013). The function of Nme1 has also expanded to some aspects of tumorigenesis (Jarrett et al 2011).…”
Section: Nme1 As Metastasis Suppressormentioning
confidence: 99%